Chagas disease knocks on our door: a cross-sectional study among Latin American immigrants in Milan, Italy. (December 2018) - Antinori, S.; Galimberti, L.; Grande, R.; Bianco, R.; Oreni, L.; Traversi, L.; Ricaboni, D.; Bestetti, G.; Lai, A.; Mileto, D.; Gismondo, M.R.; Petullà, M.; et al.
Abstract: Objectives: We aimed to assess the prevalence and risk factors for Chagas disease (CD) in Latin American immigrants and to evaluate the accuracy of diagnostic tests. Moreover, we offered to all positive subjects a complete free-of-charge clinical/instrumental evaluation as well as benznidazole treatment in order to stage the disease and verify drug tolerability. Methods: A cross-sectional survey of CD among Latin Americans living in Milan and its metropolitan area was conducted between July 2013 and July 2014. Blood samples were tested for serologic evidence of CD together with a questionnaire covering demographic and clinical-epidemiological information. Results: Forty-eight (9.6%) of the 501 tested subjects were conclusively diagnosed as having CD. The highest prevalence of CD was among those from Bolivia (43/169, 25.4%) and El Salvador (4/68, 5.9%). Older age (adjusted odds ratio (aOR)] 1.05, p =0.004), a Bolivian origin (aOR 8.80; p =0.003), being born in the department of Santa Cruz (aOR 3.72, p =0.047), having lived in mud houses (aOR 2.68; p =0.019), and having an affected relative (aOR 12.77, p =0.001) were independently associated with CD. The ARCHITECT Chagas test showed the highest sensitivity (100%) and specificity (99.8%). Twenty-nine of the subjects with CD (60.4%) underwent disease staging, 10 of whom (35.7%) showed cardiac and/or digestive involvement. Benznidazole treatment was associated with high frequency of adverse reactions (19/27, 70.4%) and permanent discontinuation (8/27, 29.6%). Conclusions: CD is highly prevalent among Bolivians and Salvadorans living in Milan. Regions with a large Latin American immigrant population should implement programmes of active detection and treatment.